Technologies for cultivation and exploitation of microalgae in industrial applications - LIMA, Serena (Università degli Studi di Palermo, 2020)
This thesis work is focused on technologies for the development of the microalgal industry. During this 3-years PhD work several themes were addressed. Section 1 consists in a literature review concerning the general features of microalgae, their composition and a description of the photosynthetic process. Furthermore, themes such as biosynthetic pathways, growth kinetics, microalgae cultivation and their applications are reviewed. Section 2 focuses on the genetic manipulation of microalgae aimed at producing a vitamin B12-enriched food supplement. In this case, the human intrinsic factor gene, was inserted in the genome of the microalgae Chlamydomonas reinardhtii in order to integrate new functions in this organism and path the way for the creation of a B12-enriched microalgal supplement. For sure, genetic engineering is going to play a role in the future of microalgal industry, but, while these technologies are developing, alternative strategies may consist in exploiting the present available photosynthetic microorganisms for obtaining the desired products. For this reason, in Section 3, flashing light as lighting strategy was explored. In fact, light energy was provided in packages to three different microalgal species, Nannochloropsis gaditana, Koliella antarctica, Tetraselmis chui, to observe the enhanced production of high-value products such as chlorophylls, carotenoids and polyunsaturated fatty acids. Furthermore, this method represents a temporal dilution of light aimed at avoiding the saturation effect. An alternative strategy for the exploitation of microalgal industry may consist in selecting and isolating indigenous species in an approach called phycoprospecting, discussed in Section 4. The concept of phycoprospecting relies on employing wastewaters as a nutrient source in order to create a sustainable process able to remediate polluted effluents while at the same time providing valuable compounds. Lastly, in Section 5 the theme of outdoor photobioreactors for the production of microalgal biomass is ...